Synthesis and biological evaluation of 2‐acylbenzofuranes as novel α‐glucosidase inhibitors with hypoglycemic activity. (3rd July 2017) - Spasov, Alexander A.; Babkov, Denis A.; Prokhorova, Tatyana Yu; Sturova, Ekaterina A.; Muleeva, Diana R.; Demidov, Maxim R.; Osipov, Dmitry V.; Osyanin, Vitaly A.; Klimochkin, Yuri N.
Abstract : A series of benzofuran derivatives was synthesized as analogues of known natural α‐glucosidase inhibitors. Their activity was evaluated in enzymatic assay and in rat model of diabetes mellitus. Newly identified inhibitors demonstrate significant potency with IC50 values ranging from 6.50 to 722.2 μm, as well as hypoglycemic activity exceeding the reference drug acarbose. Docking simulations provided insight into structure‐activity relationships to direct further development of these novel hypoglycemic agents. Abstract : A novel series of benzofuran derivatives were synthesized and evaluated as potential antidiabetic agents. Synthesized compounds show higher inhibitory activity against α‐glucosidase than acarbose. Lead compounds effectively prevents postprandial hyperglycemia in diabetic rats encouraging further structure optimizations.